1994
DOI: 10.1007/bf00797009
|View full text |Cite
|
Sign up to set email alerts
|

Sinus venosus atrial septal defect associated with vein of Galen malformations: Report of two cases

Abstract: Two unique cases are presented of infants with signs of vein of Galen malformations, whose unsuspected associated sinus venosus atrial septal defects were detected during routine echocardiography. A conservative approach to cardiac treatment is advocated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 5 publications
1
14
0
Order By: Relevance
“…In a report describing three patients with a vein of Galen malformation and sinus venosus atrial septal defect, Friedman et al hypothesised that increased superior caval return in utero may interfere with absorption of the right horn of the sinus venosus into the right atrium,3 which is thought to be the developmental defect involved in the formation of sinus venosus atrial septal defect with anomalous pulmonary venous drainage. From what is known about the timing of organogenesis, this hypothesis is plausible, assuming that absorption of the sinus venosus into the right atrium is completed around the eighth week of gestation, while the events responsible for formation of the vein of Galen malformation probably take place between 6 and 11 weeks’ gestation 2.…”
Section: Discussionmentioning
confidence: 99%
“…In a report describing three patients with a vein of Galen malformation and sinus venosus atrial septal defect, Friedman et al hypothesised that increased superior caval return in utero may interfere with absorption of the right horn of the sinus venosus into the right atrium,3 which is thought to be the developmental defect involved in the formation of sinus venosus atrial septal defect with anomalous pulmonary venous drainage. From what is known about the timing of organogenesis, this hypothesis is plausible, assuming that absorption of the sinus venosus into the right atrium is completed around the eighth week of gestation, while the events responsible for formation of the vein of Galen malformation probably take place between 6 and 11 weeks’ gestation 2.…”
Section: Discussionmentioning
confidence: 99%
“…9 McElhinney et al 10 reported partial anomalous pulmonary venous connection, ventricular septal defect and atrioventricular canal defects to be other frequent associations. Our case had pulmonary hypertension, tricuspid regurgitation and patent foramen ovale which were not structural cardiac lesions.…”
Section: Discussionmentioning
confidence: 98%
“…The onset of clinical symptoms is markedly variable‐from critically ill neonates with ischemic brain injury and life threatening cardiac failure, to asymptomatic infants and children that are diagnosed because of increasing head circumference [1–5]. Beginning with published autopsy studies in 1963 and continuing with reviews of individual institutional experience, a relationship between VGAM and congenital cardiac defects, specifically sinus venosus atrial septal defect, has gradually been recognized [4, 6–8]. Previous authors have postulated that the increased incidence of SVASD in association with VGAM was linked to the increased venous return through the superior vena cava (SVC) during development [7, 8].…”
Section: Introductionmentioning
confidence: 99%
“…Beginning with published autopsy studies in 1963 and continuing with reviews of individual institutional experience, a relationship between VGAM and congenital cardiac defects, specifically sinus venosus atrial septal defect, has gradually been recognized [4, 6–8]. Previous authors have postulated that the increased incidence of SVASD in association with VGAM was linked to the increased venous return through the superior vena cava (SVC) during development [7, 8]. This increased flow could alter the geometry, preventing the formation of the superior venosus portion of the atrial septum.…”
Section: Introductionmentioning
confidence: 99%